2017
DOI: 10.1242/jeb.160549
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic hypoxia programmes postprandial cardiovascular function in adult common snapping turtles (Chelydra serpentina)

Abstract: Reduced oxygen availability (hypoxia) is a potent stressor during embryonic development, altering the trajectory of trait maturation and organismal phenotype. We previously documented that chronic embryonic hypoxia has a lasting impact on the metabolic response to feeding in juvenile snapping turtles (Chelydra serpentina). Turtles exposed to hypoxia as embryos [10% O 2 (H10)] exhibited an earlier and increased peak postprandial oxygen consumption rate, compared with control turtles [21% O 2 (N21)]. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…The only study that measured chronic changes of pulmonary blood flow in a conscious reptile after feeding showed that the common snapping turtle, Chelydra serpentina, reduces the left to right cardiac shunt (i.e. systemic bypass of the blood flow), indicating that systemic resistance decreases more than pulmonary resistance (Wearing et al, 2017). This hints at the possibility that smooth muscle regulation during the postprandial period plays a more important role in regulating the systemic vasculature, where we observed no changes in mechanical properties of the dorsal aorta, than in the pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The only study that measured chronic changes of pulmonary blood flow in a conscious reptile after feeding showed that the common snapping turtle, Chelydra serpentina, reduces the left to right cardiac shunt (i.e. systemic bypass of the blood flow), indicating that systemic resistance decreases more than pulmonary resistance (Wearing et al, 2017). This hints at the possibility that smooth muscle regulation during the postprandial period plays a more important role in regulating the systemic vasculature, where we observed no changes in mechanical properties of the dorsal aorta, than in the pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Whether physiological adjustments that promote successful development in hypoxia‐incubated embryos affect post‐hatching performance and survival is as of yet unclear (but see Wearing, Conner, Nelson, Crossley, and Crossley ()). However, constraints on yolk utilization, and hence hatchling size, may have important fitness consequences (Sinervo, ; Warner, ).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effects of hypoxia exposure during development on phenotype and fitness at later life-history stages remain important research questions. For example, development in hypoxia has long-term effects on post-hatching cardiovascular phenotypes in snapping turtles (Chelydra serpentina; Wearing et al, 2016Wearing et al, , 2017, decreases swimming performance in snakes (Natrix maura; F.A. and J.S., unpublished results), and impacts cognitive ability in lizards (Eremias argus; Sun et al, 2014).…”
Section: Embryo Physiology and Developmentmentioning
confidence: 99%
“…Under certain conditions, oxygen restrictions can also result in depressed metabolism, decreased growth and reduced survivorship to hatching (Iungman and Piña, 2013;Warburton et al, 1995). These early developmental effects can persist into later life phenotypes (Sun et al, 2014;Wearing et al, 2017).…”
Section: Introductionmentioning
confidence: 99%